Gold medal nutrition - Cardwell, Glenn 1956- (Human Kinetics, 2012)
A practical resource for recreational and elite athletes, coaches and health professionals. Learn how to get enough protein, find the best nutritional supplements, eat to bulk up, travel well, and avoid jet lag, among other subjects.